ANALISIS GAMBAR KARYA ANAK SEKOLAH DASAR (KARAKTERISTIK GAMBAR ANAK USIA 7 – 9 TAHUN) - Rengganis, Ira (Universitas Pendidikan Indonesia, 2017)
The writing is motivated by the author's interest in the work of drawings made by children. In this paper, the image being analyzed is the work of drawings made by children aged 7 to 9 years of age or elementary school students grades 1 to 3. This research aims to know the functions and characteristics of the child in learning colleges Arts. In this study used methods of art criticism. Art criticism method consists of several stages, namely the stages of description, formal analysis, interpretation and final stage of assessment. Through the process of analysis methods of art, criticism can be concluded that the draw for children is as a medium to develop a proper sense, expression, imagination and visual communication. Arts education; Arts in children's education has an important role as an introduction and training efforts the power of expression, imagination, creativity, and artistic taste esthetics in an atmosphere of creative play. Stock images of children aged 7 to 9 have the unique characteristics of various types and properties of different images. In order to achieve the purpose of art education in elementary schools, in addition to the necessary active learning, innovative, creative, effective and fun, in the learning activities of art is in need of a teacher who understands its function in performing the procedure of learning and understanding the characteristics of children's drawings.